Is 'conflict of interest' a Misnomer? Managing interests in immunization research and evaluation. Issue 1 (31st December 2022) - McClymont, Elisabeth; Brophy, Jason; Dubey, Vinita; Kwong, Jeff; Meyer, Samantha; Crowcroft, Natasha; Halperin, Scott; MacDonald, Shannon; Simmons, Karen; Top, Karina; Ward, Brian; Sadarangani, Manish
ABSTRACT: Potential conflicts of interest in vaccine research can lead to negative consequences that undermine public trust and thereby put communities at risk. However, collaborations that may give rise to potential conflicts between interests can also greatly facilitate appropriate, scientifically robust, and timely vaccine development, implementation, and evaluation. At present, policies regarding the management of potential conflicts between interests are not ideal. To optimally manage interests in vaccine research, we recommend acknowledging all forms of interests and treating them all as relevant, developing appropriate collaborations, referring to all "conflicts of interest" simply as "interests" or "declarations, " and promoting transparency through developing consistent reporting mechanisms.